Job Finding Rate and Female Labor Supply- A Heterogeneity Perspective - Nargis .; Nooreen Mujahid (International Journal on Women Empowerment, 2019)
Background: In contemporary labor economics, the concept of job finding rate is central as it defines the job search and measures the employment potential of the labor market. Considering this fact, economists primarily count on measuring the flows of labor between the labor market states. The study is an endeavour to design a conceptual framework to determine female labor supply considering these labor market flows and job finding rate in Pakistan. Methodology: The study evaluates various search models and provides a comprehensive review of literature taking into consideration job finding rate and female labor supply. Electronic databases including Google Scholar & Medline were used. Articles, books, and conference proceedings were cited using keywords like Job Finding rate, female labor and labor market, etc. Result: The study has introduced the perspective of heterogeneity to incorporate the composition effect and dispersion effect of the labor market. The framework of the study provides a hint for policy makers to consider the relevant flows for improvement in female employment in Pakistan. Conclusion: The main conclusion stresses on including the inactive group to link up the job finding rate with female labor supply. Not doing so would bias the imputed importance of factors shaping aggregate participation and unemployment rates.